Who Takes the Floor and Why - Brescoll, Victoria L. (Administrative Science Quarterly, 2011)
Although past research has noted the importance of both power and gender for understanding volubility—the total amount of time spent talking—in organizations, to date, identifying the unique contributions of power and gender to volubility has been somewhat elusive. Using both naturalistic data sets and experiments, the present studies indicate that while power has a strong, positive effect on volubility for men, no such effect exists for women. Study 1 uses archival data to examine the relationship between the relative power of United States senators and their talking behavior on the Senate floor. Results indicate a strong positive relationship between power and volubility for male senators, but a non-significant relationship for female senators. Study 2 replicates this effect in an experimental setting by priming the concept of power and shows that though men primed with power talk more, women show no effect of power on volubility. Mediation analyses indicate that this difference is explained by women’s concern that being highly voluble will result in negative consequences (i.e., backlash). Study 3 shows that powerful women are in fact correct in assuming that they will incur backlash as a result of talking more than others—an effect that is observed among both male and female perceivers. Implications for the literatures on volubility, power, and previous studies of backlash are discussed.